Silicon modifies C:N:P stoichiometry, and increases nutrient use efficiency and productivity of quinoa - Lata-Tenesaca, Luis Felipe [UNESP]; de Mello Prado, Renato [UNESP]; de Cássia Piccolo, Marisa; da Silva, Dalila Lopes [UNESP]; da Silva, José Lucas Farias [UNESP] (Springer Nature, 2021)
Recognizably, silicon has a beneficial effect on plant growth and productivity. In this respect, it is also known that the C, N and, P stoichiometric ratios and nutrient conversion efficiency allow identifying the interactions between elements while helping to understand the role Si plays in plant growth. This study aims to investigate whether increasing Si concentrations (0, 1, 2, and 3 mmol L−1) supplied in the nutrient solution is uptaken by quinoa, modifies the C:N:P stoichiometry while increasing nutritional efficiency and crop productivity as well. Our results revealed that the Si supply by promoting a decline in the C levels, associated with greater uptake of N and P, especially decreased the C:N and C:P ratios, favoring the C metabolism efficiency, and modulated the N and P use efficiency for biomass accumulation. This improved nutritional performance and greater use efficiency of C directly favored quinoa productivity. The future perspective is to encourage new field studies with this species to adjust silicon fertilization management to different soils aiming at enhancing quinoa productivity on a sustainable basis.